The Impact of Infertility on Daily Occupations and Roles - Collins, Megan (Journal of Reproduction & Infertility, 2019)
Background: Infertility impacts approximately 16% of couples in the United States- roughly five million individuals. Experiencing infertility takes a physical and psychological toll on the infertile individual, as well as his/her partner. The goal of the current study was to explore and provide better insight into how infertility affects the roles and daily occupations (Such as self-care and work related tasks) of females. This information can better assist health care providers in providing quality care to such clients. Methods: 21 participants, females ranging in age from 20 to 46 years and experiencing infertility, participated in this qualitative, phenomenological research study. They partook in two telephone interviews aimed at exploring how infertility has impacted their roles and daily occupations. Inductive content data analysis was utilized to analyze the data. Results: Findings resulted in three main themes. Quotes from participants were used to title the themes. They are "when you’re dealing with infertility, every aspect of your life is impacted by it", "infertility impacted my areas of interest in life" and "infertility is very lonely". Conclusion: Infertility has the potential to impact every area of a female’s life. The emotional impact infertility may have on women, in addition to the physical and time constraints involved with pursuing fertility treatments, frequently resulted in decreased occupational engagement and fulfillment of roles as spouse or friend. Those experiencing infertility need more resources and support to navigate their journey.